OF HUNTING DOVES AND PIGEONS: Aristotle Reading Plato and Parmenides. On Thinking and Being are the Same - Berchman, Robert (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2020)
What does Parmenides mean by thinking and being are the same? How does Plato read Parmenides and why does Aristotle’s interpretation of Parmenides and Plato matter? Such questions hinge on how many meanings do the Greek words identity and relation signify? Three paradigms emerge from these readings: Parmenides proposes a numerical identity and a se relation of thinking and being; Plato maps a qualitative identity and per se relation of thinking and being; and Aristotle offers a pros hen numerical identity and a se relation of thinking and being.